Keabsahan Perubahan Alokasi Anggaran Bantuan Langsung Tunai Corona Virus Disease 2019 (Covid-19) Di Desa Waimangit Kabupaten Buru - Facey, Yunita Sari; Tjiptabudy, Jantje; Bakarbessy, Andress Deny (Faculty of Law, Universitas Pattimura, 2024)
Introduction: This study discusses the validity of the Waimangit Village Head's decision to stipulate the Village Regulation on Village APB Changes in 2020 without coordinating with BPD, the Village Head then changed the village budget post that was previously budgeted for the provision of social safety net in the Village in the form of BLT as a manifestation of efforts to handle the impact of COVID-19 by the central government in the Village. The budget item is used to cover the shortfall in village spending for the development of Village-Owned Enterprises.Purposes of the Research: To analyze and identify the validity and legal consequences of changes in the budget allocation of Direct Cash Transfer (BLT) intended to deal with Corona Virus Disease 2019 (Covid-19) in Waimangit village, Buru Regency based on applicable legal provisions.Methods of the Research: This research use the Normative Juridical research method which is carried out by examining primary and secondary legal materials that are relevant to the problem under study.Results of the Research: The results of the study are related to the validity of changes in the budget allocation of Corona Virus Disease 2019 (Covid-19) Direct Cash Transfer (BLT) in Waimangit Village, Buru Regency has been valid based on applicable legal provisions because it meets aspects of authority. The decision of the Waimangit Village Head in determining changes to the Village APB does not meet the requirements of procedure and substance which means that the decision remains valid but has the legal effect that it can be canceled and not binding and ends after it is canceled or there is a cancellation by a judge or by the agency authorized to cancel it.